FEATURES OF TEACHING ACADEMIC WRITING TO STUDENTS OF TECHNICAL SPECIALTIES - Borysova, Zoia; Borysova, Vira (SWorld-Ger Conference proceedings, 2025)
The article examines the peculiarities of teaching academic writing to students of technical specialties, including engineering, information technology, and software engineering. It analyzes the challenges associated with developing academic writing skill